Applications of Computational Intelligence: Third IEEE Colombian Conference, ColCACI 2020 Cali, Colombia, August 7–8, 2020 Revised Selected Papers - Orjuela Cañón, Alvaro David; Lopez, Jesus; Arias Londoño, Julián David; Figueroa García, Juan Carlos (Springer, 2021)
The computational intelligence (CI) area is increasingly employed in engineering problems in the Latin America (LA) region. LA scientists have focused their efforts on the CI field as a way to deal with problems of interest for the international community but also of great impact in the LA region. Many different areas including optimization of energy and transportation systems, computer-aided medical diagnoses, bioinformatics, mining of massive data sets, robotics and automatic surveillance systems, among many others, are commonly addressed problems from this part of the world, because of the great potential those applications could also have in developing countries. In its third edition, the IEEE Colombian Conference on Computational Intelligence (IEEE ColCACI 2020) was fortified with contributions from scientists, engineers and practitioners working on applications/theory of CI techniques. In this version of IEEE ColCACI, we received 65 papers by authors from 8 countries, and accepted 28 oral presentations in virtual mode due to the COVID-19 pandemic. In this way, the conference was an international forum for CI researchers and practitioners to share their recent advancements and results. The present proceedings include the best 12 papers presented as extended versions of the works exhibited at the conference, attending to this call for extended selected versions in these difficult times. We will continue working on offering an excellent IEEE ColCACI in future editions. Finally, we would like to thank the IEEE Colombia Section, the IEEE Computational Intelligence Colombian Chapter, the IEEE Computational Intelligence Society, the Universidad Autónoma de Occidente, the Universidad del Rosario, the Universidad Distrital Francisco José de Caldas and the Universidad de Antioquia. Also, special thanks to all volunteers, participants, and the whole crew that worked together to have a successful conference. See you at IEEE ColCACI 2021!

El área de inteligencia computacional (IC) se emplea cada vez más en problemas de ingeniería en la región de América Latina (AL). Los científicos de AL han centrado sus esfuerzos en el campo de la IC como una forma de abordar problemas de interés para la comunidad internacional pero también de gran impacto en la región de AL. Muchas áreas diferentes, incluyendo la optimización de sistemas de energía y transporte, diagnósticos médicos asistidos por computadora, bioinformática, minería de conjuntos masivos de datos, robótica y sistemas de vigilancia automática, entre muchos otros, son problemas comúnmente abordados en esta parte del mundo, debido al gran potencial que esas aplicaciones también podrían tener en países en desarrollo. En su tercera edición, la Conferencia Colombiana IEEE sobre Inteligencia Computacional (IEEE ColCACI 2020) se fortaleció con contribuciones de científicos, ingenieros y profesionales que trabajan en aplicaciones/teoría de técnicas de IC. En esta versión de IEEE ColCACI, recibimos 65 artículos de autores de 8 países y aceptamos 28 presentaciones orales en modo virtual debido a la pandemia de COVID-19. De esta manera, la conferencia fue un foro internacional para que los investigadores y profesionales de IC compartieran sus últimos avances y resultados. Las presentes actas incluyen los 12 mejores trabajos presentados como versiones extendidas de los trabajos exhibidos en la conferencia, atendiendo a esta convocatoria de versiones extendidas seleccionadas en estos tiempos difíciles. Continuaremos trabajando para ofrecer un excelente IEEE ColCACI en futuras ediciones. Por último, nos gustaría agradecer a la Sección IEEE Colombia, al Capítulo Colombiano de Inteligencia Computacional IEEE, a la Sociedad de Inteligencia Computacional IEEE, a la Universidad Autónoma de Occidente, a la Universidad del Rosario, a la Universidad Distrital Francisco José de Caldas y a la Universidad de Antioquia. Además, un agradecimiento especial a todos los voluntarios, participantes y a todo el equipo que trabajó en conjunto para tener una conferencia exitosa. ¡Nos vemos en IEEE ColCACI 2021!
Keywords: Inteligencia computacional - Congresos, conferencias, etc.; Computational intelligence - Congresses, conferences, etc.; Ingeniería informática - Congresos, conferencias, etc.; Computer engineering - Congresses, conferences, etc.; Bioingeniería - Congresos, conferencias, etc.; Bioengineering - Congresses, conferences, etc.